Preservation of musical memory in Alzheimer's disease. Issue 12 (December 1989) - Crystal, H A; Grober, E; Masur, D
Abstract : An 82 year old musician with Alzheimer's disease (AD) showed a preserved ability to play previously learned piano compositions from memory while being unable to identify the composer or titles of each work. He also showed a preserved ability to learn the new skill of mirror reading while being unable to recall or recognise new information. Both anterograde and retrograde procedural memory may be relatively spared in AD.